Two Poplar-Associated Bacterial Isolates Induce Additive Favorable Responses in a Constructed Plant-Microbiome System - Timm, Collin M.; Pelletier, Dale A.; Jawdy, Sara S.; Gunter, Lee E.; Henning, Jeremiah A.; Engle, Nancy; Aufrecht, Jayde; Gee, Emily; Nookaew, Intawat; Yang, Zamin; Lu, Tse-Yuan; Tschaplinski, Timothy J.; et al. (Frontiers in Plant Science, 2016)
The biological function of the plant-microbiome system is the result of contributions from the host plant and microbiome members. The Populus root microbiome is a diverse community that has high abundance of β- and γ-Proteobacteria, both classes which include multiple plant-growth promoting representatives. To understand the contribution of individual microbiome members in a community, we studied the function of a simplified community consisting of Pseudomonas and Burkholderia bacterial strains isolated from Populus hosts and inoculated on axenic Populus cutting in controlled laboratory conditions. Both strains increased lateral root formation and root hair production in Arabidopsis plate assays and are predicted to encode for different functions related to growth and plant growth promotion in Populus hosts. Inoculation individually, with either bacterial isolate, increased root growth relative to uninoculated controls, and while root area was increased in mixed inoculation, the interaction term was insignificant indicating additive effects of root phenotype. Complementary data including photosynthetic efficiency, whole-transcriptome gene expression and GC-MS metabolite expression data in individual and mixed inoculated treatments indicate that the effects of these bacterial strains are unique and additive. These results suggest that the function of a microbiome community may be predicted from the additive functions of the individual members.